2000
DOI: 10.1002/(sici)1521-3765(20000515)6:10<1731::aid-chem1731>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Electrostatics of Cell-Membrane Recognition: From Natural Antibiotics to Rigid Push-Pull Rods

Abstract: The question why pore-forming, alpha-helical natural antibiotics are not toxic is discussed within the general context of the interaction of electrostatically asymmetric "nanorods" with neutral, anionic, and polarized bilayer membranes. We suggest that simplification of the structural complexity of natural systems will be necessary to ultimately define the involved subtle balance between constructive and destructive electrostatic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…[28,29] On the other hand, Q 1 > Q 2 is consistent with a central location, [28] while Q 1 $ Q 2 directly reveals a transmembrane orientation in the unique case of rigid-rod fluorophores. [29,30] The latter situation (Q 1 $ Q 2 , Figure 2 a) was found for 1 (namely, rigid-rod b-barrel 1 6 , Figure 1). The changes of oligo(p-phenylene) emission as a function of relative concentrations and time further revealed that about sixty lipids per rod 1 are needed to assure complete incorporation (Figure 2 c) and that this process is finished in less than a minute (Figure 2 b).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…[28,29] On the other hand, Q 1 > Q 2 is consistent with a central location, [28] while Q 1 $ Q 2 directly reveals a transmembrane orientation in the unique case of rigid-rod fluorophores. [29,30] The latter situation (Q 1 $ Q 2 , Figure 2 a) was found for 1 (namely, rigid-rod b-barrel 1 6 , Figure 1). The changes of oligo(p-phenylene) emission as a function of relative concentrations and time further revealed that about sixty lipids per rod 1 are needed to assure complete incorporation (Figure 2 c) and that this process is finished in less than a minute (Figure 2 b).…”
mentioning
confidence: 54%
“…[29] at the membrane/water interface. [8,30,31] Namely, the above direct orientational evidence proved that the permanent location of polyamines within the hydrophobic core of bilayer membranes is possible at biologically relevant concentrations.…”
mentioning
confidence: 68%
“…These labeled membranes thus carry quencher Q 1 and Q 2 at defined distances d 1 (5.8 ) and d 2 (12.2 ) from the center of the EYPC bilayer, respectively ( Figure 1). [29,30] The latter situation (Q 1 $ Q 2 , Figure 2 a) was found for 1 (namely, rigid-rod b-barrel 1 6 , Figure 1). [28,29] On the other hand, Q 1 > Q 2 is consistent with a central location, [28] while Q 1 $ Q 2 directly reveals a transmembrane orientation in the unique case of rigid-rod fluorophores.…”
mentioning
confidence: 54%
“…The development of design strategies for the construction of easily variable active sites at the inner surface of transmembrane pores is the first step toward such organic chemistry within confined anisotropic space. In sharp contrast to breathtaking progress being made with biotechnologically modified natural pores (1), reliable and general design strategies for synthetic ion channels and pores with easily variable internal active sites do not exist (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Reasonably straightforward covalent synthesis of barrel-like macromolecules with the required Ϸ3.5-nm height and variably functionalizable interior of Ն1.0 nm diameter is not (yet) possible.…”
mentioning
confidence: 99%
“…Reasonably straightforward covalent synthesis of barrel-like macromolecules with the required Ϸ3.5-nm height and variably functionalizable interior of Ն1.0 nm diameter is not (yet) possible. The more straightforward noncovalent syntheses (16)(17)(18)(19)(20) applied to barrellike supramolecules with ion channel activity is, with one possible exception (15), limited by apparent difficulties to position functional groups at internal concave surfaces (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, we have recently found that this trend toward ''peripheral crowding'' in supramolecular synthesis (16)(17)(18)(19)(20) can be bypassed in artificial ␤-barrels with p-octiphenyl ''staves'' and have used their rationally designed hydrophobic, ionophoric, and cationic interior to encapsulate guests with complementary characteristics in water and bilayer membranes (21,22).…”
mentioning
confidence: 99%